Defining the role of fire in alleviating seed dormancy in a rare Mediterranean endemic subshrub - Cross, Adam; Paniw, M.; Ojeda, F.; Turner, Shane; Dixon, Kingsley; Merritt, David (OXFORD UNIV PRESS, 2017)
© The Author(s) 2017. Fire is a topical issue in the management of many ecosystems globally that face a drying climate. Understanding the role of fire in such ecosystems is critical to inform appropriate management practices, particularly in the case of rare and ecologically specialized species. The Mediterranean heathlands are highly fire-prone and occur in a biodiversity hotspot increasingly threatened by human activities, and determining the reproductive thresholds of at-risk heathland species is critical to ensuring the success of future conservation initiatives. This study examined the germination biology of the threatened carnivorous subshrub Drosophyllum lusitanicum, with specific focus on the role of fire-related cues (heat and smoke) in combination with seasonal temperatures and moisture conditions to determine how these factors regulate seed dormancy and germination. We found that D. lusitanicum produces water-permeable, physiologically dormant seeds with a fully developed, capitate embryo that when fresh (~1 month old) and without treatment germinate to 20-40 % within 4-8 weeks. Seeds possess a restricted thermal window (15-20 °C) for germination and a neutral photoblastic response. Seed dormancy was overcome through precision nicking of the seed coat ( > 90 % germination) or by short exposure to dry heat (80 or 100 °C) for 5-30 min (60-100 % germination). We propose seedling emergence from the soil seed bank may be cued by the passage of fire, or by soil disturbance from the movement and browsing of animals. Long-term population viability is likely to be contingent upon appropriate management of the persistent soil seed bank, as well as the adequate management of key ecological disturbances such as fire. Drosophyllum lusitanicum faces an increasingly bleak future in the absence of conservation and management initiatives aimed at reducing habitat fragmentation in heathlands and aligning fire management and livestock practices with biodiversity outcomes.